Peroxisomes Implicated in the Biosynthesis of Siderophores and Biotin, Cell Wall Integrity, Autophagy, and Response to Hydrogen Peroxide in the Citrus Pathogenic Fungus Alternaria alternata - Wu, Pei-Ching; Chen, Yu-Kun; Yago, Jonar I.; Chung, Kuang-Ren (Frontiers in Microbiology, 2021)
Little is known about the roles of peroxisomes in the necrotrophic fungal plant pathogens. In the present study, a Pex6 gene encoding an ATPase-Associated protein was characterized by analysis of functional mutations in the tangerine pathotype of Alternaria alternata, which produces a host-selective toxin. Peroxisomes were observed in fungal cells by expressing a mCherry fluorescent protein tagging with conserved tripeptides serine-lysing-leucine (SKL) and transmission electron microscopy. The results indicated that Pex6 plays no roles in peroxisomal biogenesis but impacts protein import into peroxisomes. The number of peroxisomes was affected by nutritional conditions and H2O2, and their degradation was mediated by an autophagy-related machinery termed pexophagy. Pex6 was shown to be required for the formation of Woronin bodies, the biosynthesis of biotin, siderophores and toxin, the uptake and accumulation of H2O2, growth and virulence, as well as the Slt2 MAP kinase–mediated maintenance of cell-wall integrity. Adding biotin, oleate and iron in combination fully restored the growth of the pex6-deficient mutant (Δpex6), but failed to restore Δpex6 virulence to citrus. Adding purified toxin could only partially restore Δpex6 virulence even in the presence of biotin, oleate and iron. Sensitivity assays revealed that Pex6 plays no roles in resistance to H2O2 and superoxide, but plays a negative role in resistance to 2-chloro-5-hydroxypyridine (a hydroxyl radical-generating compound), eosin Y and rose Bengal (singlet oxygen-generating compounds), and 2,3,5‐triiodobenzoic acid (an auxin transport inhibitor). The diverse functions of Pex6 underscore the importance of peroxisomes in physiology, pathogenesis and development in A. alternata.